2002
DOI: 10.1016/s1470-0328(02)01046-7
|View full text |Cite
|
Sign up to set email alerts
|

Low dose acetylsalicylic acid in prevention of pregnancy-induced hypertension and intrauterine growth retardation in women with bilateral uterine artery notches

Abstract: Objective To evaluate the efficacy of low-dose acetylsalicylic acid in the prevention of pregnancy-induced hypertension and intrauterine growth retardation in high-risk pregnancies as determined by transvaginal Doppler ultrasound study of the uterine arteries at 12 to 14 weeks of gestation. Design Randomised, double blind and placebo-controlled trial.Setting The Department of Obstetrics and Gynaecology, Tampere University Hospital, Finland.Population One hundred and twenty pregnant women considered to be at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 13 publications
4
61
0
4
Order By: Relevance
“…These findings were consistent with some recent studies regarding ASA therapy for prevention of preeclampsia, following uterine artery Doppler studies, which showed tendency towards benefit (29). In a study on 86 high-risk women with abnormal Doppler findings in 12-14 weeks of pregnancy, aspirin treatment resulted in lowering the risk of preeclampsia from 37.2% in the placebo group comparing to 11.6% in the aspirin group (34). In another study by Bower et al on women with abnormal uterine artery flow velocity waveforms, there was 29% incidence of preeclampsia in the ASA group and 41% in the placebo group, showing a significant difference (25).…”
Section: Discussionsupporting
confidence: 91%
“…These findings were consistent with some recent studies regarding ASA therapy for prevention of preeclampsia, following uterine artery Doppler studies, which showed tendency towards benefit (29). In a study on 86 high-risk women with abnormal Doppler findings in 12-14 weeks of pregnancy, aspirin treatment resulted in lowering the risk of preeclampsia from 37.2% in the placebo group comparing to 11.6% in the aspirin group (34). In another study by Bower et al on women with abnormal uterine artery flow velocity waveforms, there was 29% incidence of preeclampsia in the ASA group and 41% in the placebo group, showing a significant difference (25).…”
Section: Discussionsupporting
confidence: 91%
“…19 The study of Bujold and et al 18 confirms this hypothesis, because the papers dealing with early aspirin treatment consistently show a positive effect, with a relative risk ranging from 0.07 to 0.63 for pre-eclampsia and from 0.20 to 1 for IUGR. [20][21][22][23][24][25][26][27] The present study is the largest to date with respect to the number of patients and the only one to administer aspirin at such an early point of gestation. In accordance with previous observations, we show that aspirin diminishes the risk of developing a hypertensive gravidic disease by threefold and delays the time of delivery by almost 2 weeks, thus increasing the birth weight by more than 150 g. The risk of maternal complications was also reduced, and the risk of fetal complications was reduced by B10-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Third, factors other than PGI 2 / TXA 2 imbalance contribute to the pathogenesis of PE (Reslan and Khalil, 2010). Other causes of the negative or partially positive results with aspirin in PE may be related to the timing and dosage of aspirin (Vainio et al, 2002;Walsh, 2004). Late initiation of treatment with aspirin may not prevent the development of PE, because placental implantation is already established by week 18 of gestation (Vainio et al, 2002).…”
Section: A Prostacyclin Metabolism In Preeclampsiamentioning
confidence: 99%
“…Other causes of the negative or partially positive results with aspirin in PE may be related to the timing and dosage of aspirin (Vainio et al, 2002;Walsh, 2004). Late initiation of treatment with aspirin may not prevent the development of PE, because placental implantation is already established by week 18 of gestation (Vainio et al, 2002). In addition, aspirin at 50 to 60 mg/day is effective in inhibiting TXA 2 production by platelets but not that by placental trophoblasts or maternal leukocytes (Walsh, 2004).…”
Section: A Prostacyclin Metabolism In Preeclampsiamentioning
confidence: 99%